3D features in the calendering of thermoplastics: A computational investigation. Issue 7 (14th August 2013) - Polychronopoulos, Nickolas D.; Sarris, Ioannis E.; Papathanasiou, T.D.
<x xml:space="preserve">Abstract</x> We present results of a fully three‐dimensional computational study of the calendering process of thermoplastics using the fluid dynamics software OpenFOAM. Our aim is to elucidate unique 3D features of the process, such as spreading and melt flow. We assume that the material is fed in the form of a sheet of finite thickness and detaches from the cylinders at a prescribed thickness. The rotational motion of the cylinders, the consequent pressure build‐up (both in the machine and the transverse directions) and the presence of the free surfaces (sides) of the calendered sheet—both deformable and at ambient pressure—forces the thermoplastic melt to spread in the transverse direction. A decoupled iterative procedure is used to predict the shape of the spreading side surfaces under different conditions. A spiraling transverse flow pattern in the melt feeding section is shown to exist, which determines the actual flow path of the calendered material in a nonintuitive way. We show that insofar as the material redistribution (from the fed sheet to the produced film) during the process is concerned, the results of the present analysis predict a 3D spiral flow pattern and a redistribution of the fed material from the central region of the fed sheet to the sides of the calendered product. POLYM. ENG. SCI., 54:1712–1722, 2014. © 2013 Society of Plastics Engineers